THE USE OF BUSUU APPLICATION TO TEACH PHRASAL VERB - Fadhila, Syarifah Laila; Salam, Urai; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study evaluates the effectiveness of using the Busuu application to teach phrasal verbs to Class X MIA 3 students at SMAN 1 Sungai Raya. Employing a pre-experimental design, the research focused on 35 students from a population of 420. Data collection included pretests and post-tests, following a sequence of pre-test, treatment using the Busuu app, and post-test. Statistical analysis revealed that students"™ performance significantly improved after the treatment. The mean score increased from 67.51 in the pre-test to 79.65 in the post-test. A t-test result of 8.74 exceeded the critical value in the t-table, confirming a statistically significant difference. These results support the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (H0), indicating that integrating the Busuu application as a teaching tool effectively enhances students"™ understanding of phrasal verbs. The study concludes that digital tools like Busuu can be a beneficial supplement in language instruction.